Brand Ambassador, Purchase Interest And Testimonies On Online Purchase Decisions In Instagrams In Students In Pandai Sikek Village - Fitri Mawita; Febsri Susanti (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to examine the influence of brand ambassadors, purchase intention and testimonials on decisions online purchases on Instagram for students in the pandai sikek village. This type of research is quantitative, where this research uses numerical data and the research process emphasizes measuring objective results using statistical analysis. The population in this study were students in the pandai sikek village who had made online purchases on Instagram. The sampling technique used is non-probability sampling with purposive sampling method based on certain criteria, namely students who have done online shopping on Instagram, the number of samples is 100 people obtained using the Lemeshow formula. The data analysis technique used multiple linear regressions test using SPSS version 16.00. The hypothesis is tested using the t test at α = 0.05. The results of this study indicate that brand ambassadors, purchase interest and testimonials have a positive and significant effect on online purchase decisions on Instagram for students in the pandai sikek village.